2017
DOI: 10.1177/0003319717730942
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Alprostadil Against Contrast-Induced Nephropathy Inpatients With Renal Insufficiency Undergoing Percutaneous Coronary Intervention

Abstract: We investigated the preventive effect of alprostadil on contrast-induced nephropathy (CIN) in patients with renal insufficiency undergoing percutaneous coronary intervention (PCI). A total of 300 patients with creatinine clearance (crCl) ≤60 mL/min undergoing PCI were randomly assigned to alprostadil or a control group. The primary end point was the incidence of CIN defined as an increase in serum creatinine (Scr) levels by ≥0.5 mg/dL or≥ 25% after administration of the contrast media within 72 hours. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…26 A recent study demonstrated the preventive effects of alprostadil on the development of CIN in patients with renal insufficiency undergoing percutaneous coronary intervention (PCI). 27…”
Section: Discussionmentioning
confidence: 99%
“…26 A recent study demonstrated the preventive effects of alprostadil on the development of CIN in patients with renal insufficiency undergoing percutaneous coronary intervention (PCI). 27…”
Section: Discussionmentioning
confidence: 99%
“…The qualified articles were then downloaded for detailed assessment. Finally, data for 5495 patients extracted from 36 articles 25 –60 were used in this meta-analysis. A total of 2746 patients were in the experimental group and 2749 patients were in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…All 36 studies were RCTs and mentioned that a randomization method was used, but some of the articles described the blind method. 25 –60 Selective reporting of the results, incomplete data outcome, and other biases in the articles were low. The literature quality score is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The first was a multivariate logistic regression analysis to assess the association of BMI with V/CrCl>3, excluding the 3832 patients with complex lesions (PCI of the left main coronary artery, type C lesion, bifurcation lesion, chronic total occlusion lesion, Rotablator use, multivessel PCI) because lesion complexity may affect CV [ 28 , 29 ]. Second, we analyzed associations with CV, V/CrCl ratio, and BMI for the 3283 patients with a CrCl <60 mL/min (indicative of a high CI-AKI risk) in a subgroup analysis [ 22 , 30 ].…”
Section: Methodsmentioning
confidence: 99%